The Relantionship of Knowledge to The Use of BPJS Health Cards in The Community at Teluk Tiram Public Health Center Banjarmasin: KNOWLEDGE, BPJS - Ningsih, Novita Dwi Widiya; Della; Karinda, Merlin; Rifqiannor (Program Studi D3 Rekam Medis dan Informasi Kesehatan, 2025)
BPJS Kesehatan is a national social security program that functions to provide comprehensive health protection for the Indonesian people. The utilization of BPJS Kesehatan cards is greatly influenced by of knowledge, ease of access, and public awareness in using health services. The research was conducted to ensure relation between knowledge and the utilization of BPJS Kesehatan cards in the community at Teluk Tiram Banjarmasin Health Center in 2025. The species of research conducted was quantitative research in with an analytical survey using a cross-sectional approach. The sample consisted of 98 people as active BPJS Kesehatan participants at Teluk Tiram Health Centre. Sampling technique is Purposive sampling. Data analysis using Univariate and Bivariate analysis tests. The Pearson Correlation test analysis stated that the p-value of the knowledge variable obtained p-value = 0.015, and perception p-value = 0.004 towards the used of BPJS Kesehatan services in Teluk Tiram Banjarmasin Health Center. The study found a relationship between knowledge and BPJS Kesehatan card utilization at Teluk Tiram Community Health Centre in 2025. The study concluded is that BPJS Kesehatan card utilization at the Teluk Tiram Community Health Centre in Banjarmasin has been optimal. The community health center is expected to continue improving outreach, education, and service quality to ensure more equitable utilization of the program.